(untitled) (Research, Society and Development, 2020)
In 2019 in Wuhan city (China), is was outbreak about a novel coronavirus, causes an infections respirator, in children and adults, and is new condition was call for COVID-19. The present study being about herbal medicines and their correlation with diseases on respiratory tract basically COVID-19. To date, there are no studies showing how Ginseng Radix cooperated with the prevention or for to treat coronavirus diseases, so the aimed the present study was a to analyze in literature about this. The aim is to observe the correlation about the Ginseng Radix as a future treatment in novel coronavirus. The present study is a fruit of a review integrative of literature, where the keywords was search in databases Pubmed and Scielo.org, the keywords (Herbal medicines, Ginseng radix and Coronavirus infections) are presents in DeCS. The herbal medicines are famous alternative therapeutic for the treatment a most diseases, when used the herbal medicines for various diseases, being diseases cardiology, immunology, and too tract respiratory. The use for the herbal medicines is a secular practice, and we found a most popular, but is present study is about the ginseng radix. Ginseng is an herbal medicine derived from the root of the panax, and your use is described since the first millennium, your properties are preventing many diseases, including cancer, hypertension, and others, described in the literature. The Ginseng radix is an herbal medicine be used in the treatment for the children and adults, the problems for the tract respiratory, and exists a guideline specific for the herbal medicines and the use in clinical practice.